[Review of the book The Time of the Cannibals: On Conspiracy Theory and Context. Elisabeth Anne Davies] - Kouros, Theodoros (My University, 2024)
n this groundbreaking and well written monograph, Rakopoulos undertakes a pioneering exploration into the intricate realm of the Citizenship by Investment (CBI) program of the Republic of Cyprus (RoC). This seminal work stands out as the first monograph to scrutinize comprehensively a phenomenon not confined to the borders of the RoC or the European Union, that of the so-called "golden passports"—schemes that grant citizenship rights to people who invest a certain amount of money in the country that grants the citizenship. Driven by meticulous ethnographic research and an anthropologist's discerning eye for detail and meaning, Rakopoulos's narrative not only dissects the operational mechanics of the RoC's CBI program but also untangles the complex web of social, cultural, and economic implications entwined with the commodification of citizenship.